Burden of orofacial pain in a socially deprived and culturally diverse area of the United Kingdom. Issue 7 (July 2018) - Joury, Easter; Bernabe, Eduardo; Gallagher, Jennifer E.; Marcenes, Wagner
Abstract : Abstract: Little is known about the burden and impact of orofacial pain in deprived areas, and whether it mediates the relationship between socioeconomic position and impacts on daily life. We analysed data from a representative sample of 2168 adults, aged 16 to 65 years, from the East London Oral Health Inequality study. Participants completed a validated questionnaire on demographics, socioeconomic position (area deprivation), orofacial pain (by anatomical site) in the past month, and impacts related to oral conditions on daily life. Negative binomial regression models with robust variance estimator were fitted. The prevalence of orofacial pain was high (30.2%). The most common subset of orofacial pain was intraoral pain (27.5%). The prevalence of pain related to temporomandibular disorders was 6.8%. The most common subsets of intraoral pain were tooth (20.4%) and gingival (11.4%) pain. Orofacial pain, its subsets (intraoral and temporomandibular disorder–related pain), and intraoral pain subsets (tooth and gingival pain) consistently showed associations with all dimensions of impacts on daily life that were highly statistically significant: functional limitation, psychological discomfort, disabilities, and handicap. Socioeconomic inequalities were present in orofacial pain and some dimensions of impacts on daily life. Orofacial pain did not mediate the relationship between area deprivation and impacts on daily life. Our study demonstrated a substantial burden and impact of orofacial pain in a socially deprived and culturally diverse area of the United Kingdom. To address this burden, interventions that lie within the remit of health services are needed to improve access to dental care for adults with orofacial pain. Abstract : The burden of orofacial pain in deprived areas is high and has a substantial impact on daily life: functional limitation, psychological discomfort, disabilities, and handicap.